2019
DOI: 10.1016/j.freeradbiomed.2018.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant redox signalling and stress response in age-related muscle decline: Role in inter- and intra-cellular signalling

Abstract: Age-associated frailty is predominantly due to loss of muscle mass and function. The loss of muscle mass is also associated with a greater loss of muscle strength, suggesting that the remaining muscle fibres are weaker than those of adults. The mechanisms by which muscle is lost with age are unclear, but in this review we aim to pull together various strands of evidence to explain how muscle contractions support proteostasis in non-muscle tissues, particularly focussed on the production and potential transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 143 publications
0
19
0
Order By: Relevance
“…According to the bioinformatics analyses results, we found that HSF1 might be the direct targeting gene of miR-455-3p. HSF1 is the transcription factor primarily responsible for the transcriptional response of cells to physical and chemical stress, which assist in refolding or degrading damaged proteins 22, 23. HSF1 activation is accomplished at the post-translational modification and protein-protein interaction level 24 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the bioinformatics analyses results, we found that HSF1 might be the direct targeting gene of miR-455-3p. HSF1 is the transcription factor primarily responsible for the transcriptional response of cells to physical and chemical stress, which assist in refolding or degrading damaged proteins 22, 23. HSF1 activation is accomplished at the post-translational modification and protein-protein interaction level 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been reported that oxidizing free radical species (ORS) are generated during aerobic bouts [13]. Skeletal muscles generate Super Oxide and Nitric Oxide which is increased by muscle contraction activity [14]. ROS is essential for skeletal muscle force generation, however, ROS in high values may reduce muscle contraction properties and thus, result in early exhaustion [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…While there is still much to elucidate regarding the desensitization of redox circuitry, a modeling paper published in 2018 suggested that persistently elevated levels of stress or inflammation lead to “molecular habituation”, which leads to the desensitization of essential adaptive pathways [55]. Elevated levels of ROS (the signal) impair redox signaling by disrupting the initiation (via a sensor) of an adaptive response to the stress, thereby impairing the ability to functionally adapt to the stress [64,65]. Aged individuals have higher resting levels of ROS production, and they also have an impaired ability to acutely increase ROS to elicit an adaptive response [62,66].…”
Section: Redox Circuits and Redox Homeostasismentioning
confidence: 99%